Mundane Circular Economy Policy: Peta Kebijakan dan Kriteria Sekolah Sirkular di Level Pendidikan Dasar - Yuana, Suci Lestari (Indonesian Perspective, 2023)
This research introduces the concept of "Mundane Circular Economy Policy" (MCEP) in the study of International Political Economy (IPE) and explains how this paper relates to broader IR issues such as sustainability, global economic dynamics, and global education policies. The research methodology employed is Multi Criteria Mapping, which analyzes complex and uncertain issues like Circular Schools. Through the participation of 22 primary school principals in Central Java, three outputs were generated from this research: (1) a map of circular school policies, highlighting 58 policy initiatives that implement the 5R principles (Reduce, Rethink, Reuse, Repair, Recycle); (2) a map of assessment criteria for circular policies; and (3) a mapping of optimism and pessimism in implementing the 5R principles in circular schools. These outputs have significant implications within the context of IPE, as they demonstrate how schools can act as agents in creating economically and politically sustainable environments.